Late Quaternary Ecosystems and Humans in Northern Patagonia: New Results from Cueva Huenul 1 (Neuquén, Argentina) - Pompei, María de la Paz (2012)
The Cueva Huenul 1 (CH1) archaeological site provides one of the first dated sequences of stratified sediments spanning the Late Pleistocene-Early Holocene transition in the northern end of Patagonia (Fig. 1). Preliminary stratigraphic and chronological data has been presented previously, allowing defining two sets of layers separated by an erosive unconformity: the Late Pleistocene layers (units V-VIII), mainly composed of fossil dung and bracketed between dates of 13,844 ± 75 and 11,841 ± 56 RCYBP; and the Holocene layers (units I-IV), composed by aeolian sediment and bracketed between dates of 9531 ± 39 and 1416 ± 37 RCYBP (Barberena et al. 2010). The 9531 ± 39 date comes from a hearth right on top of the unconformity, and provides evidence for the earliest human presence at CH1. In this advance report we present a preliminary palynological and archaeological study of the stratigraphic units spanning the Pleistocene-Holocene transition (units IV-VIII, Quadrat A1, 2 x 1 m). The excavation was conducted using 10-cm extraction levels (the stratigraphic units discussed here correspond to extraction levels 5-8).